Predictability of ASEAN-5 Exchange Rates in the Post-Crisis Era - Liew, Venus Khim-Sen; Ahmad Zubaidi, Baharumshah (UPM, 2003)
Five ASEAN currencies are investigated in an attempt to determine whether the post-crisis ASEAN exchange rates are more predictable by the US dollar or Japanese yen. Results suggest that prior to the 1997/1998 Financial Crisis, all exchange rates were better predicted by the US dollar as the base currency. The post-crisis Singapore exchange rate continues to be better predicted in US dollar. On the other hand, Japanese yen better predicted other post-crisis ASEAN exchange rates.